2008
DOI: 10.1021/ef8003587
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Flame-Front Characteristics of Conical Turbulent Lean Premixed Methane/Air Flames

Abstract: Lean Premixed Combustion (LPC) is recently proposed in gas turbine combustors which have been operated traditionally in the non-premixed mode. In this method, fuel and air are mixed before entering the combustor. With LPC, the flame temperature is reduced due to the operating with excess air conditions. Thus, thermal NO x can be reduced to negligible levels at these lean conditions. On the other hand, the local and global flame extinction risks and therefore flame instabilities may arise because of operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(52 reference statements)
2
2
0
Order By: Relevance
“…The turbulent flame speed increases with the Re λ and at a constant k in the inlet region, in accordance with eq. (10). In all cases tested, U t initially decreases from the turbulence dynamics, as expected, and then suddenly increases within the flame zone.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The turbulent flame speed increases with the Re λ and at a constant k in the inlet region, in accordance with eq. (10). In all cases tested, U t initially decreases from the turbulence dynamics, as expected, and then suddenly increases within the flame zone.…”
Section: Resultssupporting
confidence: 78%
“…al. [10]. They used CH 4 -air flames with an equivalence ratio, Φ, of 0.6, 0.7, and 0.8, the k-ε turbulence model, and a perforated flame holder to stabilize the flame.…”
Section: Introductionmentioning
confidence: 99%
“…It assumes that the flow is fully turbulent, and the effects of molecular viscosity are negligible. The realizable k-ε turbulence model is therefore valid for fully turbulent flows, consistent with the flow characteristics in a typical combustion chamber [17].…”
Section: 20 Modeling Meshing and Boundary Conditionsupporting
confidence: 65%
“…The turbulent flow field is simulated using the k –ε turbulence model with Pope correction . Several versions of this turbulence model have been evaluated for cold flow . It was concluded that the turbulence model with Pope correction results in better agreement with experiments comparing in-chamber mean and turbulent flow field statistics.…”
Section: Numerical Studiesmentioning
confidence: 99%